European foreign policy in an evolving international system the road towards convergence - Casarini, Nicola 1971-; Musu, Costanza 1970 (Palgrave studies in European Union politics, 2007)
Providing an assessment of European foreign policy since Maastricht, this title analyzes the level of policy convergence achieved by EU member states in crucial areas and regions of the world.